PERAN PEMERINTAH DAN MODAL SOSIAL TERHADAP KESEJAHTERAAN RUMAH TANGGA MISKIN DI KECAMATAN GEROKGAK KABUPATEN BULELENG - sukrisna, igusti agung; Sudibia, I Ketut; Budiasa, I Gde Sudjana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.01.TAHUN 2018DO - 10.24843/EEB.2018.v07.i01.p07, 2018)
Gerokgak district has a majority of poor households in Buleleng regency. The number of poor households in this district tendsto increase significantly. The government has tried to overcome the poverty and improve the welfare of poor households in this district by launching various programs on poverty but has not been able to lower the poverty rate. By considering the previous background, the aims of this study areto analyze the effect of the government's role and social capital toward the welfare of poor households in district of Gerokgak, Buleleng regency. This research was conducted in the district of Gerokgak,Buleleng regency on the 40 heads of poor households, where each village was taken some samples according to the population of poor households. This study uses a quantitative analysis approach that are supported by diskritif and qualitative things. After analyzed by using PLS SEM analysis . It si concluded that :(1) There is a positive and significant  influence of the government's role toward the norms of social capital, 2) There is a positive and significant influence of the government's role toward the social networks of social capital, 3) There is positive and significant government influence toward the trust of social capital, 4) There is positive and significant impact of  norms of social capital on the welfare of poor households, 5) There is positive and significant  influence of networks of social capital toward the welfare of poor households, 6) There is a mediation on the role of government to the welfare of poor households through the constructs norms of social capital, 7) There is mediation on the role of government toward the welfare of poor households through the construct of social capital networks.